2022
DOI: 10.1007/s13201-021-01501-6
|View full text |Cite
|
Sign up to set email alerts
|

Blend of natural coagulants as a sustainable solution for challenges of pollution from aquaculture wastewater

Abstract: Dependency on sea food has increased owing to its nutrition as well as being complete food. As the production of seafood is enhanced through aquaculture, wastewater release has also improved. The composition of wastewater from aquaculture production has been a concern as it has oil and grease, organic content, etc., which makes its treatment challenging. The present study aims at treating aquaculture wastewater using two natural coagulants—chitin and seeds of Moringa oleifera. The efficiency of the natural coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In this context, natural coagulants represent a viable, nature-based solution for water treatment. Derived from natural sources like plants, they are readily accessible, cost-effective, simple to apply, biodegradable, non-toxic, environmentally friendly, efficient, and result in lower sludge volumes [9]. This makes them particularly suitable for rural areas, where economical and eco-sensitive water treatment methods are essential.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, natural coagulants represent a viable, nature-based solution for water treatment. Derived from natural sources like plants, they are readily accessible, cost-effective, simple to apply, biodegradable, non-toxic, environmentally friendly, efficient, and result in lower sludge volumes [9]. This makes them particularly suitable for rural areas, where economical and eco-sensitive water treatment methods are essential.…”
Section: Introductionmentioning
confidence: 99%
“…Using chemical treatments followed by DAF, these authors reported on up to 97% removal of the poultry wastewater COD. In the study of Karnena, Konni, Dwarapureddi, and Saritha, 9 depuration of fish processing water using coagulation/flocculation alone provided 92% COD reduction using a combination of Tanfloc, FeCl 3 , and Zetag.…”
Section: Introductionmentioning
confidence: 99%
“…Using chemical treatments followed by DAF, these authors reported on up to 97% removal of the poultry wastewater COD. In the study of Karnena, Konni, Dwarapureddi, and Saritha, 9 depuration of fish processing water using coagulation/flocculation alone provided 92% COD reduction using a combination of Tanfloc, FeCl 3 , and Zetag. Although the mentioned studies were successful in wastewater depuration, the use of nonfood-grade chemicals limited the application of the recovered sludge to feedstock for biogas production purposes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that a natural coagulant like Moringa oleifera (MO) can be utilized to treat effluent from aquaculture mainly to remove ammoniacal nitrogen, phosphorus, and turbidity [18][19][20]. Treatment sequence of wastewater using MO seeds by coagulationflocculation to sedimentation-filtration showed maximum turbidity and elimination of suspended materials.…”
Section: ■ Introductionmentioning
confidence: 99%